1981
DOI: 10.1677/joe.0.0880147
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Low Phosphorus and Low Calcium Diets of Duodenal Absorption of Phosphate in Betamethasone-Treated Chicks

Abstract: Although the inhibitory effect of glucocorticoids on the intestinal absorption of calcium is well recognized, their effect on the absorption of phosphate is less well documented. We studied the effect of the oral administration of betamethasone (BM; 25 micrograms/kg per day) on the duodenal absorption of phosphate in chicks fed normal calcium, normal phosphorus (NCaNP), normal calcium, low phosphorus (NCaLP) or low calcium, normal phosphorus (LCaNP) diets using the ligated loop technique in vivo. The daily ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Chickens receiving a diet with normal P (0.65%) and normal Ca (1.20%) absorbed less than 50% of 47 Ca. Duodenal P absorption in 15 to 20 d-old chicks that had been fed a low Ca or a low P diet for eight d, as measured by ligated duodenal loop technique in vivo, increased by 49 and 87%, respectively (Fox et al, 1981). Blahos et al (1987) reported an increase in duodenal and ileal P absorption in broiler chickens fed a low Ca diet for two wk and a smaller, but still significant increase in duodenal but not ileal P absorption in chicks fed a low P diet.…”
Section: Early Dietary Adaptationmentioning
confidence: 99%
“…Chickens receiving a diet with normal P (0.65%) and normal Ca (1.20%) absorbed less than 50% of 47 Ca. Duodenal P absorption in 15 to 20 d-old chicks that had been fed a low Ca or a low P diet for eight d, as measured by ligated duodenal loop technique in vivo, increased by 49 and 87%, respectively (Fox et al, 1981). Blahos et al (1987) reported an increase in duodenal and ileal P absorption in broiler chickens fed a low Ca diet for two wk and a smaller, but still significant increase in duodenal but not ileal P absorption in chicks fed a low P diet.…”
Section: Early Dietary Adaptationmentioning
confidence: 99%
“…Interestingly, the inhibition of P transport by glucocorticoid was only observed when dietary Ca and P are normal. Low P or low Ca diets that stimulates P absorption by the production of l,25(OH) 2 D 3 was unaffected by the administration of glucocorticoid (Fox et al 1981).…”
Section: Glucocorticoidsmentioning
confidence: 97%